PENGARUH PROFITABILITAS, FREE CASH FLOW, INVESTMENT OPPORTUNITY SET TERHADAP DIVIDEND PAYOUT RATIO - Prasetio, Djoko Adi; Suryono, Bambang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
positive and significant influence to the dividend payout ratio on automotive companies which are listed inIndonesia Stock Exchange.This research is a quantitative research type and the population is all automotivecompanies which are listed in Indonesia Stock Exchange during the 4 year periods started from 2011 to 2014.The sample collection technique has been done by using saturated sample methods, therefore 13 automotivecompanies which are listed in Indonesia Stock Exchange during the 4 years periods which start from 2011 to2014 have been selected as samples. The data analysis technique has been done by using multiple linearregressions and the hypothesis test has been done by performing SPSS 20 version. Based on the result of modelfeasibility test, it shows that the regressions model that has been generated is feasible and it can be used forfurther analysis.Based on the result of the hypothesis test, it shows that profitability, free cash flow andinvestment opportunity set variables have positive and significant influence to the dividend payout ratio in theautomotive companies which are listed in Indonesia Stock Exchange.Keywords: profitability, free cash flow, investment opportunity set, dividend payout ratio.